Heterostructured Mo‐Doped CoP on MXene Supports Enhanced the Alkaline Hydrogen Evolution Activity. Issue 19 (17th May 2022) - Zhao, Jiafu; Luo, Shaojuan; Chen, Yonghui; Zhu, Runxian; Liang, Jinyi; Wang, Fei; Fu, Xiaobo; Wu, Chuande
Abstract: The development of safe, efficient, and non‐noble‐metal electrocatalysts is a promising approach for hydrogen energy production. However, due to low electrical conductivity and weak stability, non‐noble metal catalysts for HER are significantly limited in practice. Here, a method for low‐cost catalysts was reported for synthesizing Mo‐CoP/Ti3 C2 T x composites in which Mo‐doped CoP materials were facilely grown on the surface of Ti3 C2 T x MXene. The introduction of MXene and the doping of Mo promoted electron transfer and increased the active sites compared with CoP. As HER electrocatalysts, the Mo‐CoP/Ti3 C2 T x materials exhibited a good HER activity with a low overpotential of only 117 mV. What's more, these catalysts had shown excellent electron conductivity, fast catalytic dynamics, and a boosted electrochemical active surface. Suitable synthetic ratios were obtained by optimizing the MXene substrate and the Mo doping amount. This work provided a new guide for the design and exploration of MXene based electrocatalysts. Abstract : The introduction of MXene substrates and the defect formation by molybdenum doping effectively enhance the electrons transportation in the Mo‐CoP/Ti3 C2 T x composite. Mo‐CoP/Ti3 C2 T x possesses efficient HER activity with a low η 10 of 117 mV in an alkaline medium, as well as fast catalytic kinetics of 84.6 mV ⋅ dec −1, low charge transfer resistance of 12 Ω, and boosted active sites of 3.96 mF ⋅ cm −2 . Also, the composite was engaged with satisfying stability caused by the stable phosphate species on the Mo‐CoP nanoparticles.